Social Concertation in Times of Austerity European Integration and the Politics of Labour Market Governance in Austria and Switzerland - Afonso, Alexandre (Changing Welfare States, 2013)
Why do governments still negotiate with trade unions and employers in the design of labour market and welfare reforms despite the steady decline of trade union membership almost everywhere in Europe? Social Concertation in Times of Austerity investigates the political underpinnings of social concertation in this new context with a focus on the regulation of labour mobility and unemployment protection in Austria and Switzerland. It shows that the involvement of organised interests in policymaking is a strategy of compromise-building used by governments when they are faced with party-political divisions, or when unpopular reforms are likely to have risky electoral consequences.